Identification of Factors Causing Turnover Intention in Employees - Irlangga, Sulthan Alief; Hasanati, Nida (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Turnover intention is an important issue that impacts organizational stability, especially in the midst of changing demographics and labor market dynamics. This study aims to identify the factors that cause turnover intention through a Systematic Literature Review (SLR) based on PRISMA guidelines and the SPIDER framework. The search was conducted on Scopus, ScienceDirect, PubMed, and Google Scholar databases, with 10 articles selected through screening using the Rayyan application. The analysis showed that turnover intention is influenced by various multidimensional factors, such as job satisfaction, leadership style (authentic and transformational), job stress, attachment, and social climate such as exclusion. Supervisor support, perceived organizational benevolence, and job satisfaction act as mediators or moderators in the relationship. The findings emphasize the importance of a holistic approach in employee retention strategies that not only focuses on compensation, but also creating a supportive work environment and effective leadership.